Determinación de las ventajas, desventajas y el campo de aplicación de las certificaciones internacionales en el área de proyectos - Gallego Rengifo, Mauricio (Universidad de San Buenaventura - Cali, 2017)
There are a number of international project management bodies that have created and distributed different standards, which serve as a guide to good practice and a common reference in project management; Therefore, the work shows the most internationally known. The objective of this work was to identify the advantages, disadvantages and the field of application of the international certifications in the area of ​​projects. The methodology used in the study plan was qualitative, taking into account the information collected from the authors consulted through which it was possible to identify variables and covariables for the collection of information that indicated that the research of this study is descriptive. The research was carried out by reviewing and analyzing various texts, grade papers, articles, standards and guides.